Ten-year follow-up of Parkinson's disease patients randomized to initial therapy with ropinirole or levodopa - Hauser, Robert A.; Rascol, Olivier; Korczyn, Amos D.; Jon Stoessl, A.; Watts, Ray L.; Poewe, Werner; De Deyn, Peter P.; Lang, Anthony E. (Movement disorders, 2007)
In a 5‐year, double‐blind study, subjects with Parkinson's disease (PD) who were randomized to initial treatment with ropinirole had a significantly lower incidence of dyskinesia compared with subjects randomized to levodopa, although Unified Parkinson's Disease Rating Scale (UPDRS) motor scores were significantly more improved in the levodopa group. Subjects who completed the original study were eligible to participate in a long‐term extension study conducted according to an open, naturalistic design and were evaluated approximately every 6 months until they had been followed for a total of 10 years. Comparing subjects randomized to initial treatment with ropinirole (n = 42) and levodopa (n = 27), the incidence of dyskinesia was significantly lower in the ropinirole group (adjusted odds ratio [OR] = 0.3; 95% confidence interval [CI]: 0.1, 1.0; P = 0.046) and the median time to dyskinesia was significantly longer (adjusted hazard ratio = 0.4; 95% CI: 0.2, 0.8; P = 0.007). The incidence of at least moderate wearing off (“off” time ≥26% of the awake day) was also significantly lower in the ropinirole group (adjusted OR = 0.3; 95% CI: 0.09, 0.03; P = 0.03). There were no significant differences in change in UPDRS activities of daily living or motor scores, or scores for the 39‐item PD questionnaire, Clinical Global Impression, or the Epworth Sleepiness Scale. Early treatment decisions for individual patients depend largely on the anticipated risk of side effects and long‐term complications. Both ropinirole and levodopa are viable treatment options in early PD. © 2007 Movement Disorder Society